2020
DOI: 10.3390/ani10112100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vivo and In Vitro Digestibility in Donkeys

Abstract: We compared in vivo and in vitro dry matter (DM) and neutral detergent fiber (NDF) digestibility in donkeys using feces as microbial inoculum. Four donkeys were used in a 4 × 4 Latin square design with a 2 × 2 factorial arrangement of treatments. The animals were fed two types of hay, with or without flaked barley. For the in vivo procedure, total feces were collected for 6 days from each donkey; digestibility was calculated as the difference between ingested and excreted DM and NDF. For the in vitro procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The digestibility values observed in the trial were in the range reported for rabbit diets [ 9 ]. Higher values were observed in vivo than in vitro, as already found in rabbit [ 7 ], in horse [ 20 ] and donkey [ 23 ] respectively. Statistical differences were observed with the fecal inoculum only, while with the multienzyme the results were similar to the in vivo data.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The digestibility values observed in the trial were in the range reported for rabbit diets [ 9 ]. Higher values were observed in vivo than in vitro, as already found in rabbit [ 7 ], in horse [ 20 ] and donkey [ 23 ] respectively. Statistical differences were observed with the fecal inoculum only, while with the multienzyme the results were similar to the in vivo data.…”
Section: Discussionsupporting
confidence: 65%
“…For each method, a linear regression analysis (PROC REG, procedure in SAS) was used to assess: (1) the relationships between in vivo and in vitro digestibility; (2) the regression equations for predicting the in vivo digestibility from each in vitro method. Reproducibility of the methods was calculated as reported by Tassone et al [ 23 ] and it was expressed as coefficient of variation (SD/mean × 100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method has as its weaknesses, including the need to use cannulated animals as cecal microflora donors. An alternative that replaces ruminal or cecal fluid and does not require surgical intervention is the use of equine feces, since they have fermentable activity that allows for their use as an inoculum for in vitro fermentation studies [ 13 , 14 ]. While the technique used by Theodorou et al [ 14 ] initially relied on rumen fluid as a source of microbial inoculum, the use of feces has proven to be a successful alternative source of microbial inoculum in ruminant, equid, and other non-ruminant studies.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, accurate measurement of the ME values of any given diet requires the execution of in vivo digestibility trials with animals, and sometimes the measurement of the Gross Energy (GE) of feed, feces, urine and methane. Most such measurements can only be made in research centers specially prepared to do so, as well as being costly; consequently, to solve these difficulties, some approaches to estimated energy concentrations from nutrient composition or in vitro digestibility measurements have been proposed [26,27]. Because of the relative constancy of both the GE of digestible organic matter for most forages other than silage and the proportions of energy lost in urine and methane, highly significant correlations are normally found between ME and organic matter digestibility (OMD), such that approximate conversions of in vitro OMD (IVOMD) values to ME values may be made [28].…”
Section: Introductionmentioning
confidence: 99%